Innate immune function during antineoplastic treatment is associated with 12-months survival in non-small cell lung cancer - Ryssel, Heidi; Egebjerg, Kristian; Nielsen, Susanne Dam; Lundgren, Jens; Pøhl, Mette; Langer, Seppo W.; Kjaer, Andreas; Ostrowski, Sisse Rye; Fischer, Barbara Malene (Frontiers in Immunology, 2022)
Introduction The immune system has proven to be a key player in the progression as well as containment of cancer with new treatment strategies based on immunotherapy targeting this interaction. Assessing immune function could reveal critical information about the immune response to therapeutic interventions, revealing predictive biomarkers for tailored care and precision medicine. Methods We investigated immune function in 37 patients with inoperable non-small cell lung cancer (NSCLC) undergoing treatment with PD-L1 immune checkpoint inhibitor (ICI), chemotherapy (CT) or chemo-radiotherapy (CT/RT). Blood samples before (day 0) and during therapy (day 7, 21 and 80) were investigated by a standardized immunoassay, TruCulture®. Results Outcomes revealed a developing innate immune response induced by both immunotherapy and chemotherapy. NSCLC-patients displayed evidence of chronic innate immune activation and exhaustion prior to treatment. This pattern was particularly pronounced during treatment in patients dying within 12-months follow-up. Compared to treatment with CT, ICI demonstrated a higher ex vivo-stimulated release of proinflammatory cytokines. Discussion These preliminary findings may pave the way for tailored treatment and immune-monitoring.